2014
DOI: 10.1007/s10620-014-3289-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Liver X Receptor Correlates with Intrahepatic Inflammation and Fibrosis in Patients with Nonalcoholic Fatty Liver Disease

Abstract: LXR expression correlated with the degree of hepatic fat deposition, as well as with hepatic inflammation and fibrosis in NAFLD patients. Our research suggests that LXR is an attractive target for treatment and regulation of hepatic inflammation and fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 20 publications
2
81
1
1
Order By: Relevance
“…Three nuclear transcription factors regulating cholesterol metabolism have been linked to NAFLD: sterol regulatory element-binding protein (SREBP-2), farnesoid X receptor (FXR), and liver X receptor (LXR) [33]. LXR regulates hepatic triglyceride and cholesterol metabolism in rodents; increased expression of hepatic LXR in humans has been reported [34]; our western blotting results showed increased LXR expression in high-fat and high-cholesterol diet rat, which was reversed by perilla oil supplementation. FXR was the master regulator of bile acid synthesis [35]; it suppresses bile acid synthesis by inhibiting CYP7A1 via inducing intestinal epithelial expression of FGF15 [36]; perilla oil increased FXR expression in POH, which was inhibited in HFD.…”
Section: Discussionmentioning
confidence: 99%
“…Three nuclear transcription factors regulating cholesterol metabolism have been linked to NAFLD: sterol regulatory element-binding protein (SREBP-2), farnesoid X receptor (FXR), and liver X receptor (LXR) [33]. LXR regulates hepatic triglyceride and cholesterol metabolism in rodents; increased expression of hepatic LXR in humans has been reported [34]; our western blotting results showed increased LXR expression in high-fat and high-cholesterol diet rat, which was reversed by perilla oil supplementation. FXR was the master regulator of bile acid synthesis [35]; it suppresses bile acid synthesis by inhibiting CYP7A1 via inducing intestinal epithelial expression of FGF15 [36]; perilla oil increased FXR expression in POH, which was inhibited in HFD.…”
Section: Discussionmentioning
confidence: 99%
“…Higuchi et al (2008) reported that LXRa acts as one of the main regulators of lipid metabolism by regulating SREBP-1c expression in patients with NAFLD. According to our recent study investigating the association between LXRa and NAFLD in human, the positive rate of LXRa expression was 30% in control, 50% in NAFLD, and 97% in NASH group (Ahn et al, 2014). In high-fat dietinduced steatosis animal model, expression of hepatic LXRa was increased significantly from the first day of high-fat feeding that was lasted for weeks .…”
Section: Discussionmentioning
confidence: 98%
“…LXR is one of the most important regulators of de novo lipogenesis; it induces transcriptional activation of Fas, Acc, and Scd-1, both directly and indirectly, via mechanisms involving SREBP-1c and carbohydrate response element binding protein (Liang et al, 2002;Chen et al, 2004). LXRa expression levels in NAFLD patients tend to be higher than those of controls (Ahn et al, 2014). Increases in hepatic fatty acid uptake and enhanced de novo lipogenesis are of prime importance in the development of hepatic steatosis; lipid disposal via oxidation and export are only moderately affected in patients with this condition (Lewis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…LXR expression correlated with the degree of hepatic fat deposition, as well as with hepatic inflammation and fibrosis in NAFLD patients (60). Furthermore, GW3965 suppresses markers of fibrosis and stellate cell activation in primary mouse stellate cells (55).…”
Section: Role Of Nuclear Receptors In Hepatic Inflammation and Fibrosismentioning
confidence: 99%